On the 'Disclosure Initiative – Principles of Disclosure': The EAA Financial Reporting Standards Committee's View. (2nd January 2020) - Abad, Cristina; Barone, Elisabetta; Gullkvist, Benita M.; Hellman, Niclas; Marques, Ana; Marton, Jan; Mason, Stephani; Silva, Ricardo Luiz Menezes; Morais, Ana; Moya Gutierrez, Soledad; Quagli, Alberto; Vysotskaya, Anna
Abstract: This paper summarises the contents of a comment letter produced by a working group of 12 academics in response to the International Accounting Standards Board (IASB) Discussion Paper on principles of disclosure. The comment letter was submitted by the Financial Reporting Standards Committee (FRSC) of the European Accounting Association (EAA). The work includes reviews of relevant academic literature of areas related to the various questions posed by the IASB in the Discussion Paper, including the 'disclosure problem' and the objective of the project, the suggested principles of effective communication, the roles of the primary financial statements and notes, the location of information and the use of performance measures. The paper also discusses the disclosure of accounting policies, the objectives of centralised disclosure, and the New Zealand Accounting Standards Board staff's approach to disclosure.